Head-and-neck solid tumors in children: A retrospective review from a tertiary care institute in North India - Ravi Sankar Manogaran; Ankur Mandelia; Govind Bhuskute; Arulalan Mathialagan (Wolters Kluwer Medknow Publications, 2021)
Objectives: The aim of this study was to review the clinical profile, management, and outcome of solid tumors in the head-and-neck region in children at our institute. Methods: We retrospectively reviewed children with head-and-neck solid tumors who were treated jointly under the departments of Pediatric Surgery and Otorhinolaryngology at our institute between 2016 and 2019. Results: In the study period, 10 children (6 males, 4 females) with a median age of 9.5 years (range 5 days-16 years) were treated by our unit. The patients had four tumors arising from the parotid, 2 from nose/naso-pharynx, 1 each from the tongue, submandibular gland, para-pharyngeal space, and infratemporal fossa. A majority (90%) of the patients underwent complete surgical excision of the tumor, preserving the loco-regional neurovascular structures to minimize postoperative morbidity. Malignant lesions were seen in 4 patients (2 rhabdomyosarcoma, 1 primitive neuro-ectodermal tumor, 1 mucoepidermoid carcinoma) and 6 patients had benign pathology (3 pleomorphic adenoma, 2 mature teratoma, 1 schwanomma). Additional therapy with chemotherapy and local radiotherapy was required in 3 out of 4 patients with malignant pathology. The median follow-up duration is 15 months. At last follow-up, all patients are alive and 9 out of 10 patients (90%) are disease-free. Conclusion: Our experience highlights rare and difficult tumors in the head-and-neck region in children. These tumors are not commonly managed by the pediatric surgeon in routine practice. The paper outlines the multi-modality management of these tumors, which is essential for an optimal outcome.